Ekspresi Gerak Ikan Dengan Media Sampah Plastik Dalam Penciptaan Karya Seni Patung - Arsana Putra, I Made Deny; Jodog, I Made; Rinu, Ni Made (Program Studi Seni Murni ISI Bali, 2022)
Research on the creation of this work of art with this paper is intended to turn plastic waste, which is currently a serious problem, increasingly polluting the environment of rivers and waterways. This environmental problem prompted the author to process plastic waste into sculptures. This work raises the theme of waste to increase public awareness so as not to litter, especially in the river environment which not only disturbs the habitat of aquatic creatures but also the environment that is essential for all creatures including humans. The river environment in the writer's area has begun to be filled with plastic waste which makes the water polluted and cannot be utilized optimally. The making of this sculpture is based on the theories of sculpture including art theory, aesthetic theory, and semiotic theory. This creation uses a method of creating, knowledge transfer, technology, skills that are adapted to the needs of the author in processing plastic waste to be made into environmentally friendly sculptures and expressing fish movements.